THE EFFECT OF SOME CLIMATE CHARACTERISTICS ON LAND TRANSPORT ROUTES IN AL-MUTHANNA GOVERNORATE - Dr. Fatima Radi Sajit Al-Jabri (Scholar Express Journal, 2023)
The research dealt with the impact of some climate characteristics, including temperature, wind and climatic phenomena such as rain and dust storms on land roads, including railways, and the research contained two sections, the first section dealt with the reality of transport in Muthanna Governorate and the second section included the impact of climatic characteristics on transport routes in Muthanna Governorate and the results showed a clear impact of climate elements on transport routes, The study area is characterized by a high temperature, as it reached (46.2 m 5), which leads to smelting, deformations and pits in the asphalt used in paving the streets. And the occurrence of expansion and contraction of asphalt layers in paved roads when temperatures vary between night and day and during summer and winter, as well as its impact on the expansion of railway rails, and the winds in the study area raise dust and dust due to the lack of natural vegetation, and the lack of rain, which leads to exposure to dust storms as it is located within the areas located south of the 35th parallel north,  Dust storms blow over Iraq in the areas that fall within these circles, and the variation in rainfall in the study area leads  to damage
Keywords: transport methods, temperature, wind, rain